Planning, governance, and feasibility in brownfield-to-housing redevelopment: a case study of Salt Lake City - Roberson, Gabriel Sage (My University, 2026)
This thesis explores the processes, institutional dynamics, and planning strategies involved in redeveloping brownfields into housing in Salt Lake City, Utah. As housing demand grows and available land decreases, cities increasingly view former industrial or contaminated sites as valuable options for infill development. Although brownfields offer significant potential to boost housing supply and remediate environmental legacies, their transformation for residential use is complicated by regulatory hurdles, financial limitations, and institutional fragmentation. This research examines how these obstacles are managed in practice and highlights the key factors that affect successful brownfield-to-housing conversions. This research uses a qualitative case study method, including semi-structured interviews with planners, developers, environmental experts, nonprofit leaders, and public officials. It also involves analyzing planning documents, policies, and redevelopment programs. The analysis uses both inductive and deductive coding to identify main themes related to redevelopment feasibility, governance, and planning strategies. By focusing on stakeholder views, the study shows how redevelopment happens through real-world decision-making, negotiations, and interactions within institutions. Findings from this study show that while site conditions influence brownfield-to-housing projects, they are also greatly affected by the coordination of environmental, financial, and governance factors. Key institutional elements like interagency collaboration, administrative capacity, and regulatory consistency are essential for evaluating project viability. Stakeholders consistently see redevelopment as a collaborative yet complex effort that requires ongoing communication across different agencies and sectors. Programs such as Utah's Voluntary Cleanup Program and EPA support help reduce uncertainty and liability, although they also introduce additional procedural steps that need to be managed. The study also highlights key planning strategies that support redevelopment, including early environmental due diligence, aligning cleanup and housing finance timelines, incorporating brownfield reuse into housing policy, and employing adaptive reuse and infill development approaches. However, ongoing challenges persist, especially related to funding gaps, risk perception, and public stigma related to contaminated sites. This research advances planning scholarship by viewing brownfield redevelopment as primarily a governance and institutional coordination issue, rather than just a technical or environmental problem. It offers policy-relevant insights for mid-sized cities aiming to increase housing supply while managing environmental concerns. Emphasizing the value of collaboration, planning capacity, and strategic alignment, the study provides a framework for more effectively promoting brownfield-to-housing redevelopment in Salt Lake City and comparable urban areas.
Keywords: Planning; Policy; Housing; Brownfields; Development